Patients as qualitative data analysts: Developing a method for a process evaluation of the ‘Improving the Safety and Continuity of Medicines management at care Transitions’ (ISCOMAT) cluster randomised control trial - Powell, Catherine; Ismail, Hanif; Cleverley, Richard; Taylor, Andrew; Breen, Liz; Fylan, Beth; Alderson, Sarah L; Alldred, David P (Health expectations : an international journal of public participation in health care and health policy, 2021)
Background How to meaningfully partner with patients as data analysts remains obscure. A process evaluation of the ‘Improving the Safety and Continuity Of Medicines management at care Transitions’ (ISCOMAT) cluster randomised control trial of an intervention for improving medicines use for people living with heart failure is being conducted. The intervention includes patient held information on heart medicines and care, enhanced communication between hospital and community pharmacists, and increased engagement of community pharmacists with patient care post‐hospital discharge. ISCOMAT patients living with heart failure were interviewed about experiences with the intervention. We sought to gain insights from patients on data collected to enhance our understanding of experiences with the intervention. Objective To develop a method for involving patients as analysts of qualitative data in a process evaluation. Design Patients and researchers co‐analysed qualitative data. A framework method was applied involving; familiarisation, coding, developing an analytical framework and interpretation. The process was facilitated through home working and a workshop with a training component. Results The co‐designed framework enabled researchers to map all further patient interview data. Patients' specialist knowledge enhanced understanding of how the ISCOMAT intervention can be best implemented. Conclusions Patients’ unique experiences can enhance validity and rigour in data analysis through sharing their interpretations of qualitative data. The involvement process is crucial in elucidating knowledge and avoiding tokenism. As analysts, patients gain an appreciation of research processes, building trust between researchers and patients. Group dynamics and involving patients throughout the whole research process are important considerations.